A new brain dopamine‐deficient Drosophila and its pharmacological and genetic rescue. (23rd November 2016) - Cichewicz, K.; Garren, E. J.; Adiele, C.; Aso, Y.; Wang, Z.; Wu, M.; Birman, S.; Rubin, G. M.; Hirsh, J.
Abstract : Dopamine (DA) is a neurotransmitter with conserved behavioral roles between invertebrate and vertebrate animals. In addition to its neural functions, in insects DA is a critical substrate for cuticle pigmentation and hardening. Drosophila tyrosine hydroxylase (DTH) is the rate limiting enzyme for DA biosynthesis. Viable brain DA‐deficient flies were previously generated using tissue‐selective GAL4‐UAS binary expression rescue of a DTH null mutation and these flies show specific behavioral impairments. To circumvent the limitations of rescue via binary expression, here we achieve rescue utilizing genomically integrated mutant DTH . As expected, our DA‐deficient flies have no detectable DTH or DA in the brain, and show reduced locomotor activity. This deficit can be rescued byl ‐DOPA/carbidopa feeding, similar to human Parkinson's disease treatment. Genetic rescue via GAL4/UAS‐DTH was also successful, although this required the generation of a new UAS‐DTH1 transgene devoid of most untranslated regions, as existing UAS‐DTH transgenes express in the brain without a Gal4 driver via endogenous regulatory elements. A surprising finding of our newly constructed UAS‐DTH1m is that it expresses DTH at an undetectable level when regulated by dopaminergic GAL4 drivers even when fully rescuing DA, indicating that DTH immunostaining is not necessarily a valid marker for DA expression. This finding necessitated optimizing DA immunohistochemistry, showing details of DA innervation to the mushroom body and the central complex. When DA rescue is limited to specific DA neurons, DA does not diffuse beyond the DTH‐expressing terminals, such that DA signaling can be limited to very specific brain regions. Abstract : Dopamine (DA) is an essential neurotransmitter regulating locomotor activity and reward in humans. The DA deficiency in humans manifests as Parkinson's disease (PD), a condition caused by death of dopaminergic neurons. Here, we develop a model of brain DA deficiency in fruit flies that allows rescue with genetic methods or using PD drugs. To adequately assess the effects of neuron‐selective rescue, we greatly improved upon DA immunohistochemistry detection to directly examine diffusion of release DA. With genetic rescue of DA synthesis limited to selected neurons innervating mushroom body and central complex, regions involved in regulating learning and locomotion, respectively, we found that DA does not diffuse to surrounding neurons, even with tightly intermingled neurons. This will allow precise manipulations in future studies. Furthermore, we show that tyrosine hydroxylase, the universally used marker of catecholamine neurons, is an imperfect marker of neuronal DA expression. Our new DA deficiency model will be useful in studying DA‐modulated neuronal pathways, and the compensatory signaling mechanisms that can modulate the course of PD.